2017
DOI: 10.1088/1757-899x/245/2/022027
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Waste Basalt Powder on Selected Properties of Cement Paste and Mortar

Abstract: Abstract. Concrete is the most widely used man-made construction material in civil engineering applications. The consumption of cement and thus concrete, increases day by day along with the growth of urbanization and industrialization and due to new developments in construction technologies, population growing, increasing of living standard. Concrete production consumes much energy and large amounts of natural resources. It causes environmental, energy and economic losses. The most important material in concre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
0
13
0
3
Order By: Relevance
“…Since the properties of concrete are shaped from the moment of mixing in a process influenced by many factors, assessment of its quality (parameters) can be carried out at different times: during production, during delivery and before/after construction, and importantly, quality assessment can be performed by different participants of the investment process: the producer, the contractor, and the investor. Achieving the desired quality of concrete involves not only conformity assurance, but also appropriate design of concrete mix and selection of suitable ingredients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], proper manufacturing [ 22 , 23 , 24 ], development of innovative research methods that aid concrete design aimed at obtaining appropriate properties and durability [ 25 , 26 , 27 ] and development of methods for analysing obtained assessment results both during production and in existing constructions [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the properties of concrete are shaped from the moment of mixing in a process influenced by many factors, assessment of its quality (parameters) can be carried out at different times: during production, during delivery and before/after construction, and importantly, quality assessment can be performed by different participants of the investment process: the producer, the contractor, and the investor. Achieving the desired quality of concrete involves not only conformity assurance, but also appropriate design of concrete mix and selection of suitable ingredients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], proper manufacturing [ 22 , 23 , 24 ], development of innovative research methods that aid concrete design aimed at obtaining appropriate properties and durability [ 25 , 26 , 27 ] and development of methods for analysing obtained assessment results both during production and in existing constructions [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive use of this material for bituminous mixtures and concretes leads to the production of huge quantities of powder during the preparation of aggregates. Different studies and researches have been done for the recycling and reuse of this waste powder in replacement of raw aggregates for the production of construction materials [ 26 ]. Some researchers have also verified the AA of the basalt powder, with positive outcomes [ 27 ].…”
Section: Materials and Experimental Programmentioning
confidence: 99%
“…Dobiszewska et al, [7] used basalt powder with different variations as a substitution in materials. It was shown that 8 % of the weight concentration is optimal with respect to compressive and flexural strength.…”
Section: Introductionmentioning
confidence: 99%